Increasing Teacher Professionalism at SMK Negeri Penerbangan Aceh Through Training Scientific Writing and Scientific Work Development: Meningkatkan Profesionalisme Guru di SMK Negeri Penerbangan Aceh Melalui Pelatihan Tata Tulis Ilmiah dan Pengembangan Karya Ilmiah - Yuwaldy Away; Saminan; Rika Sri Utami; Safrizal Razali; Melinda; Muslimsyah (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2023)
SMK Negeri Penerbangan Aceh is one of the educational institutions in the Aceh region that focuses on vocational education. In this community service initiative, the team identified the challenges faced by teachers at this school, as the lack of motivation and time constraints in writing academic papers. In an effort to address these issues, the team designed and implemented a training program that encompasses academic writing techniques and the use of research software. The evaluation results show a significant improvement in the motivation, self-confidence, and knowledge of teachers related to academic paper writing. This program also facilitates collaboration among teachers, members of the team, and guest speakers. This collaboration provides emotional support and a deeper understanding of research strategies and the application of technology in developing academic papers. The contribution of this community service initiative aids teachers at SMK Negeri Penerbangan Aceh in enhancing their ability to write academic papers, which supports the requirements for promotion and professional career advancement. This training program also has the potential to be implemented in other educational institutions facing similar challenges in improving teacher professionalism.